Producing Bio Colors Without Using Synthetic Chemicals - Limal, Aakanksha (Journal of Advanced Research in Alternative Energy, Environment and Ecology; Vol 11 No 1&2 (2024): Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2024)
Many synthetic colors formed from chemicals have adverse effects on the environment. Bio colors are nowadays used in Holi festivals. Colors are also becoming an integral part of modern-day life. The use of colors is becoming a part of our everyday lives. There is a need for nontoxic colors in order to remove substances like lead, cadmium, chromium, and cobalt from the food chain. Bio-colors are mainly prepared from plant origins. The current review reports research and studies on the environmentally friendly production of colors. A natural color, like the color of unbleached fabric or unvarnished and unstained wood. A color that accurately reproduces the real color of the object shown in a photograph. Holi colors are traditionally particle powders or fluid splashes sprayed by hand, toy guns, or slamming balloons and are sourced from natural sources. Artificially produced colors pollute the environment with harmful substances like malachite green, rhodamine, gentian violet, lead oxide, copper sulfite, mercury sulfite, chromium iodide, silica, mica dust, and other adulterants used to make carrier materials attractive, or it has even been proven that such powders can be contaminated by fungi chemicals.